Porous Multiphase Microcharacteristics Research of New Cement-Based Grouting Material Concretion - Wei Xie; Junwu Xia; Linli Yu; Hongfei Chang (Advances in Civil Engineering)
As an excellent inorganic hydraulic cementitious material, new cement-based grouting material (abbreviated as NCG) has a wide application prospect in grouting engineering. Four types of water-cement ratio (W/C ratio) NCG concretions were systematically researched on the solid-phase composition, microscopic morphology, nanoscale pore characteristics and micron-scale multiphase microscopic characteristics through SEM, TGA-DSC, BET, MIP, and 3D-XRM in combination with hydration reaction mechanism. The NCG concretion is characterized as a spatial network structure formed by dendritic or columnar ettringite (AFt) crystals, filled with calcium silicate hydrate gel (C–S–H) and aluminum gel (AH3). In the solid phase, the mass of AFt is the highest, about 65%, the mass of C–S–H is about 20%, and the mass of AH3 is the least, about 15%. In nanoscale, the pore size of NCG concretion is concentrated in about 50 nm–3 μm, and the volume proportion reaches about 90%, which can be used as the characteristic parameter of pore-phase. With the increase of W/C ratio and age, the MPD of pore decreases, and the probability of the MPD-pore increases, and the dispersion of the probability of pores increases. In nanoscale, the porosity of NCG concretion is as high as 60%. With the increase of W/C ratio and age, the porosity of NCG concretion increases, but the effect on the density of solid-phase is little. In micron scale, the regular characteristics related to diameter of pore-phase and gel-phase are similar, showing a three stage formula: as their diameter increases, the number of monocases decreases and its rate of reduction gradually slows down, the volume-proportion decreases first and then increases, the differentiation of volume between the monocases increases gradually, and the differentiation between monocases shape and sphere is bigger, and its shape characteristics are more diverse and discrete.